Implementation of Integrated Learning Model in Construction Structure and Construction Management Courses - Carina, Annisa' (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to explore the application of an integrated learning model in the Construction Structure and Construction Management course, and examine how the model can improve students' readiness in using real-time data that is relevant to the needs of the construction industry. This study uses a qualitative descriptive approach with an integrated learning study method. The research location is in the Civil Engineering Study Program, Darul 'Ulum Islamic University, Lamongan. The research subjects consisted of lecturers and students who were taking related courses. This learning model was implemented through six main stages: introduction to theory, technology integration, real-time data-based project simulation, cross-disciplinary collaboration, data-based decision making, and evaluation. The results showed that students gained a better understanding of the relationship between theory and practice, and began to get used to processing and analyzing data in the context of project decision making. However, limited access to technology and lack of technical training are major challenges. The implications of these findings emphasize the importance of providing supporting infrastructure and strengthening cooperation with industry so that learning is more contextual and applicable.